Peran dan Upaya Disperkimtan dalam Mewujudkan Tertib Administrasi Pemindahan Makam di Kota Palangka Raya - Salsabila Syifana Alkamila; Ahmad Irfansyah Rosyadi; Agita Naysilla Putri; Muhammad Lexsi Pratama; Mochammad Reiza Ash-Shofi (Lembaga Pengembangan Kinerja Dosen, 2026)
The relocation of graves in Palangka Raya City often gives rise to administrative problems due to the limited availability of burial land and the public’s lack of understanding of the applicable procedures. This issue has become increasingly complex with the rising demand for grave relocations since 2025 and the implementation of Palangka Raya City Regional Regulation No. 13 of 2024, which aims to maintain order and legal certainty in the management of graves. This study aims to examine the role and efforts of the Department of Housing, Settlements and Land Affairs (Disperkimtan) in ensuring orderly administrative procedures for grave relocation, as well as to identify the obstacles encountered. The research method employed is a normative-empirical legal study using a qualitative approach, in which data was collected through observation, interviews and a literature review. The research findings indicate that the Department of Public Works and Housing plays a vital role as a regulator, provider of administrative services, data manager, and field supervisor in the grave relocation process. However, several challenges have been encountered, such as the public’s limited understanding of grave relocation procedures and the scarcity of cemetery land. To address these challenges, the Department of Public Works and Housing has undertaken various initiatives, including public awareness campaigns, streamlining service procedures, and optimising the use of cemetery land. It is hoped that this research will contribute to improving the effectiveness of grave relocation management, ensuring it is more orderly, systematic, and in accordance with applicable laws and regulations.